OPTICAL COHERENCE TOMOGRAPHY GUIDANCE IN THE MANAGEMENT OF ACUTE CORONARY SYNDROME BASED ON PLAQUE MORPHOLOGY - Abbasi, Waleed Ahmed; Khan, Hamid Sharif; Nazir, Atif; Khan, Hazrat Ullah; Abbasi, Iqra Ateeq (Journal of Ayub Medical College Abbottabad, 2021)
Background: Acute coronary syndrome (ACS) is one of the leading causes of death worldwide. It is characterized by the formation of coronary artery thrombus which can be either due to plaque rupture, plaque erosion or rupture of a calcific nodule. The aim of study was to assess the plaque morphology leading acute coronary syndrome using OCT and to guide management based on its findings. It was an observational study, conducted at Rawalpindi Institute of Cardiology from Jan to Dec 2019. Methods: Fifty patients meeting the inclusion criteria were included in the study. OCT procedure was performed following intracoronary injection of 100-150 ug of nitroglycerine. The imaging catheter (OFDI dragon view) of the OCT device (Terumo Luna wave OFDI, Tokyo, Japan) was inserted into the culprit artery. Blood clearance was achieved by injecting diluted iodinated contrast at the rate of 5 ml/sec. Imaging acquisition was obtained following automated pullback at the rate of 25 mm/sec. Pathologies like stent under deployment, mal-apposition, strut fracture, plaque erosion, plaque rupture were assessed by the operating interventionist well versed with the OCT technology and lesion assessment. Data analysis was done using the SPSS version 26. Categorical variables were presented as counts and percentages while continuous variables as mean±SD. Results: A total of 50 patients were included in the study. The mean age was 49.24±11.92. Majority of the patients were male comprising 78.0% of the cases. Plaque rupture was the most common underlying pathology seen in 32.5% of the patients and exclusively in STEMI patients which required stent deployment. Thin cap fibroatheroma was seen in 27.9% of the cases while lipid rich plaque in 23.2% of the cases; again, requiring stent deployment. 9.3% of the cases had plaque erosion while 4.6% had calcific nodule and only 2.3% had intramural hematoma which were treated conservatively. 42.8% of the stent thrombosis patients had under-deployed stents requiring balloon dilatation while 14.2% had mal-apposed stent again requiring balloon dilatation. In contrast 14.2% each had neo-atherosclerosis, stent strut fracture and uncovered stent struts as the underlying pathology for stent thrombosis each requiring stent deployment. Conclusion: OCT guided PCI in cases of acute coronary syndrome is a valuable modality that gives insight into the underlying pathology of the disease process and also guides in proper management. Keywords: Optical coherence tomography OCT; acute coronary syndrome (ACS); plaque morphology